Placental Polyp: A Case Report - Wiset Watcharotone; Chairat Leelaphatanadit (Siriraj Medical Journal, 2005)
A 28-year-old widow, gravida 1, para 1 which took place ten years earlier, presented with heavy bleeding from the vagina. Pelvic examination revealed a hemorrhagic and necrotic mass protruding from the external cervical os. Further investigations demonstrated a positive urine pregnancy test and a low titer of serum beta-hCG (53.6 mIU/ml). Ultrasonography and color Doppler imaging showed a hyperechoic and hypovascularized mass in the cervical canal. During subsequent planned tissue biopsy, the bleeding was uncontrollable, thus a total abdominal hysterectomy was performed. The pathologic findings were compatible with a placental polyp.